2017
DOI: 10.5565/rev/qpsicologia.1399
|View full text |Cite
|
Sign up to set email alerts
|

Conjugality in the Different Stages of the Family Vital Cycle

Abstract: ResumoA conjugalidade é um fenômeno dinâmico, que sofre alterações ao longo do ciclo vital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
1
3
0
4
Order By: Relevance
“…Our results showed that couple adjustment generally declined from Stage II (couple formation: the joining of families) to Stage VII (families nearing the end of life), consistent with previous research (e.g., Dush et al, 2008;Tucker & Aron, 1993;Umberson et al, 2005). In line with previous studies (VanLaningham et al, 2001;Wiltgen Tissot & Falcke, 2017), individuals in Stage III (families with young children) reported lower couple adjustment than individuals in Stage II (couple formation: the joining of families); individuals in Stage V (launching children and moving on at midlife), revealed lower couple adjustment than Stage IV (families with adolescents); and also individuals in Stage VII (families nearing the end of life) registered lower couple adjustment than individuals at Stage VI (families in late middle age). However, when evaluating couple adjustment across all stages of the family life cycle, our results shows that significant differences between stages are likely to be explained by the significant lower scores of couple adjustment in Stage VII, comparing with the other stages, except for stage V (launching children and moving on at midlife).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that couple adjustment generally declined from Stage II (couple formation: the joining of families) to Stage VII (families nearing the end of life), consistent with previous research (e.g., Dush et al, 2008;Tucker & Aron, 1993;Umberson et al, 2005). In line with previous studies (VanLaningham et al, 2001;Wiltgen Tissot & Falcke, 2017), individuals in Stage III (families with young children) reported lower couple adjustment than individuals in Stage II (couple formation: the joining of families); individuals in Stage V (launching children and moving on at midlife), revealed lower couple adjustment than Stage IV (families with adolescents); and also individuals in Stage VII (families nearing the end of life) registered lower couple adjustment than individuals at Stage VI (families in late middle age). However, when evaluating couple adjustment across all stages of the family life cycle, our results shows that significant differences between stages are likely to be explained by the significant lower scores of couple adjustment in Stage VII, comparing with the other stages, except for stage V (launching children and moving on at midlife).…”
Section: Discussionsupporting
confidence: 92%
“…Previous cross-sectional research suggests a curvilinear relationship (concave up) with couple adjustment declining in the early years of marriage and increasing in the later years, with the highest levels in pre-parental and empty-nest phases (e.g., Anderson et al, 1983;Lawson, 1988 ). Recent longitudinal research suggests that individuals reveal higher levels of marital quality in couple formation: the joining of families (Stage II 1 ), and declines over time (Dush et al, 2008;Tucker & Aron, 1993;Umberson et al, 2005), with the steepest decay occurring during the earliest and latest years of marriage (VanLaningham et al, 2001;Wiltgen Tissot & Falcke, 2017). However, it is important to note that most studies on couple adjustment and happiness over time report average trends from relatively homogenous samples with little attention to unique factors that may influence outcomes, such as cultural context, economic hardship, or generational cohort.…”
Section: Couple Adjustment and Family Life Cyclementioning
confidence: 99%
“…The form of administration of these components will have repercussions on Marital Satisfaction. For Tissot and Falcke (2017), dyadic satisfaction presented the lowest level in individuals with young children and the highest score in individuals with adolescent children.…”
Section: Discussionmentioning
confidence: 93%
“…Researchers have indicated the use of couple-specific skills to promote relationship enhancement and increase marital satisfaction (Ramos, Barreto, & Barreto, 2015;Villa & Del Prette, 2013). Tissot and Falcke (2017) identified potential sources of stress in the various stages of the family life cycle, which require the couple's involvement in certain tasks which, associated with specific risks, can produce dissatisfaction and even marital separation. Although married individuals reported more feelings of happiness than single, divorced, separated and widowed ones (Soulsby & Bennett, 2015), in Brazil, the Instituto Brasileiro de Geografia e Estatística (2015) reported an increase of 118.3% in the number of divorces between 2005-2015.…”
mentioning
confidence: 99%
“…Os elementos da qualidade conjugal, como por exemplo a paixão, o compromisso e o investimento, variam ao longo do tempo, ainda que todos constituam o relacionamento em algum momento. Desse modo, uma compreensão multidimensional da qualidade conjugal engloba a avaliação que o casal faz de todos os elementos de acordo com o contexto conjugal (Tissot & Falcke, 2017;.…”
Section: Introductionunclassified